THE COMPLEX EDUCATIONAL PROGRAMME OF THE CONTINUOUS PEDAGOGIC EDUCATION AS A SKILFULLY PEDAGOGIC TRAINING ORGANISATION MODEL ENGENEERING ECOLOGICAL TYPE STUDENTS (Pedagogy of Higher and Secondary Education, 2010)
In the article the effective organization model of skilfully pedagogic training of engeneering ecological type students through the adoption of complex educational programme of the continuous pedagogic education is grounded in theory.
Keywords: professional and pedagogical training; engineering and ecological education; technical university; complex curriculum; system